2020
DOI: 10.1001/jamanetworkopen.2020.0506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Associated With Unmet Needs in Adult Cancer Survivors in Canada

Abstract: IMPORTANCE Understanding the challenges faced by an increasing number of cancer survivors can guide the development and implementation of effective survivorship care models. OBJECTIVE To identify the physical, emotional, and practical concerns and associated unmet needs reported by cancer survivors. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional survey study obtained data from the Experiences of Cancer Patients in Transitions Study of the Canadian Partnership Against Cancer, in collaboration with cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
1
39
0
3
Order By: Relevance
“…Leaving mental health needs unattended leads to poor quality of life among PCa survivors, poor oncological outcomes, and could potentially burden health care systems (6)(7)(8)(9)(10)(11). In light of the current and recent studies, the necessity of assessing patients' needs as they emerge after the diagnosis and treatment, understanding the role treatment modalities play in their development, and creating survivorship care plans that address these needs including earlier interventions in the form of pre-habilitation as well as survivorship programs is evident (11,20,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Leaving mental health needs unattended leads to poor quality of life among PCa survivors, poor oncological outcomes, and could potentially burden health care systems (6)(7)(8)(9)(10)(11). In light of the current and recent studies, the necessity of assessing patients' needs as they emerge after the diagnosis and treatment, understanding the role treatment modalities play in their development, and creating survivorship care plans that address these needs including earlier interventions in the form of pre-habilitation as well as survivorship programs is evident (11,20,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to better understand challenges related to cancer survivorship. A comprehensive description of survey methods, development, validation, and dissemination have been published elsewhere [ 19 , 20 ]. Briefly, in 2016, 40,790 survey packages were mailed to adolescent and adult cancer patients identified through the provincial cancer agencies/registries of 10 Canadian provinces.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, respondents with a family doctor or nurse practitioner who was "very involved" in their cancer care had lower unmet physical and emotional needs. Previous research has reported that adult cancer survivors who had both a General Practitioner (GP) and oncologist involved in their survivorship care reported a higher likelihood of met needs compared to those with GPs who were not involved in their survivorship care [31]. The collaboration between oncologists and primary care providers has been highlighted as a crucial component of high-quality survivorship care [32].…”
Section: Discussionmentioning
confidence: 99%